ANALYSIS PERFORMANCE OF THE SEMARANG CITY LABOR DEPARTMENT IN THE AREA OF INCREASING AND EXPANDING EMPLOYMENT OPPORTUNITIES - Niken Nur Fitriani; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Performance is an achievement of work in an organization that is related to the satisfaction and strategic objectives of the organization. The Semarang City Manpower Office is a government agency that has the role of planning, coordinating, and fostering employment, expanding work and empowering unemployed people. issues that are happening in Semarang City are field job that available is not comparable with movement growth people, availability vacancy job is not accordance with skill or competency, job seekers are dominated by graduate high school or vocational high school so that amount of unemployed increase. The purpose of this study is to find out the performance of the Semarang City Labor Department in the area of increasing and expanding employment opportunities. the method used in this study is descriptive qualitative with a purposive technique. Data collection techniques are done by interviewing secondary data and observations. Organizational performance measurement indicators used according to Dwiyanto, namely productivity, service quality, responsiveness, responsibility, and accountability. The driving factor and inhibiting factor of organizational performance are human resources , infrastructures and teamwork factor. The recommendations given are collaborate with private suvey instutution for collecting data of job seekers and requesting fund to local government to conduct socialization activity, so that the information and training delivered to society in Semarang City.